Frequency of Surgical Outcome of Patients Who Underwent Basicervical Femur Fractures Treatment with Dynamic Hip Screw Combiner with Derotation Hip Screw at Teritay Care Hospital, Karachi - Awes Ahmed, Khalil Ahmed, Kashif Ali Shaikh, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: A basicervical fracture occurs when the femoral neck breaks below its intertrochanteric connection1. It's between a femoral neck fracture, treated with cancellous screws, and an intertrochanteric fracture, treated with sliding screws2. Previous studies revealed basicervical fractures might be treated with the DHS like intertrochanteric fractures. Basicervical fractures are less stable than intertrochanteric fractures 3,4, hence the DHS alone may not lead to a good functional outcome 5. A basal femoral neck fracture is one type of femoral fracture. Objective: To determine the frequency of surgical outcome of patients who underwent basicervical femur fractures treatment with dynamic hip screw combined with derotation hip screw at Tertiary Care Hospital, Karachi. Study Design: Descriptive Case study. Setting: This study was conducted at Department of Orthopaedic Surgery, Jinnah Postgraduate Medical Centre, Karachi, Pakistan. Duration: Six months after the approval of synopsis from August 23, 2019 to February 22, 2020. Methodology: JPMC in Karachi treated all included patients. Participants consented after learning about the study's methods, risks, and benefits. The wound was shaved and dressed the night before surgery. The patient's arms and legs were tied to the traction foot component using a fracture table. Image intensifiers were employed to verify the closed reduction. Straight cut from the greater trochanter down the thigh. Using an angle guide, a threaded guide pin was placed into the femoral head. Non-absorbable sutures closed the wound. Incision closed with suction drainage. All obtained data was kept in a performa and evaluated electronically for research. Results: Mean ± SD of age was 51.3±7.16 years. In distribution of gender, 67 (64.4%) were male while 37 (35.6%) were female. Surgical outcome was divided into two parts i.e. functional and radiological outcome. In Functional outcome 17 (16.35%) were having excellent hip score, 38 (36.55%) having good score, 22 (21.15%) having fair score while 27 (25.95%) having poor score. In radiological outcomes 33 (31.75%) had fracture reduction, 51 (49.02%) had fracture fixation, 20 (19.23%) had fracture union. Practical Implication: This study will help to determine the patient’s surgical outcomes on implying the dynamic hip screw combined with derotation hip screw, in treating basicervical femur fractures. Conclusion: It is to be concluded that DHS may allow better restoration of functional and radiological outcomes for the treatment of basicervical femur fractures in well selected patients that meet the indications for surgery whenever the technical competence and facilities exist. Keywords: Basicervical Femur Fractures, Dynamic Hip Screw, Derotation Hip Screw, Fracture, Hip Fracture